The symbolic currency of labor at the parole board - Greene, Joss (Punishment & society, 2025)
While scholars have studied labor in and after prison, we know less about the processes that connect the two. How do administrators managing the boundary between prison and the outside world evaluate criminalized people as workers? We analyze how work shapes the adjudication of suitability in 105 California parole hearings. Parole hearings frame the prison as a site of economic enhancement, increasing incarcerated people's skills and eagerness to enter the labor market. However, in parole decisions, commissioners place less emphasis on workplace readiness than on readiness for being out of work. Thus, criminalized subjects are pushed not only to cultivate work discipline, but also to cultivate the self-discipline required to endure material suffering and to interpret this experience as meaningful and under their individual control.